Effect of Intravenous Iron on Functional Capacity in Patients with Ischemic Cardiomyopathy (Journal of Invasive and Clinical Cardiology, 2024)
Background: Iron deficiency is common in heart failure with reduced ejection fraction. Intravenous (IV) iron supplementation has been found to reduce morbidity in heart failure. However, the effect of IV iron on Bangladeshi patients with heart failure are not known.Objects: The study was done to see the effect of IV iron on functional capacity in Bangladeshi patients with ischaemic cardiomyopathy (ICM) and iron deficiency.Methodology: In this quasi-experimental study, out of 80 hospitalized patients with ICM and iron deficiency, 40 were given IV ferric carboxymaltose (FCM) in addition to standard therapy of heart failure, while another 40 were randomized to standard therapy alone. Primary outcome measure was changes in six-minute walk test (6MWT) distance, while secondary outcome measures were changes in New York Heart Association (NYHA) functional class, left ventricular ejection fraction (LVEF) and plasma NT-proBNP at Weeks 4 and 12. Results: 6MWT distance improved significantly in patients receiving IV iron therapy compared to the patients not receiving IV iron. LVEF improved and plasma NT-proBNP decreased significantly in IV irontreated patients than in patients receiving standard therapy. However, improvement in NYHA functional class was not statistically significant.Conclusion: In Bangladeshi patients with ICM and iron deficiency, IV FCM on top of standard heart failure therapy was associated with improved functional capacity.J Inv Clin Cardiol 2023; 5(2): 32-37